2020
DOI: 10.1101/2020.04.26.20081307
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fast SARS-CoV-2 detection protocol based on RNA precipitation and RT-qPCR in nasopharyngeal swab samples

Abstract: The SARS-CoV-2 pandemic has evolved far more aggressively in countries lacking a robust testing strategy to identify infected individuals. Given the global demand for fast and reliable diagnosis to determine the carrier individuals, a stock-out scenario for a number of essential reagents/kits used along the diagnostic process has been foreseen by many organizations. Having identified the RNA extraction step as one of the key

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…A shortage of commercial RNA extraction kits has motivated many laboratories to find in-house extraction methods: such as Trizol-based purification [18] and RNA precipitation with isopropanol. [19] At least four groups have shown that the RNA extraction step can be omitted, yielding results with minimal change in sensitivity. [20] Reverse transcription and amplification: Reverse transcription is a standard step that uses the enyzme reverse transcriptase to convert RNA into complementary DNA.…”
Section: Overview Of the Genetic Testing Protocols And Innovationsmentioning
confidence: 99%
“…A shortage of commercial RNA extraction kits has motivated many laboratories to find in-house extraction methods: such as Trizol-based purification [18] and RNA precipitation with isopropanol. [19] At least four groups have shown that the RNA extraction step can be omitted, yielding results with minimal change in sensitivity. [20] Reverse transcription and amplification: Reverse transcription is a standard step that uses the enyzme reverse transcriptase to convert RNA into complementary DNA.…”
Section: Overview Of the Genetic Testing Protocols And Innovationsmentioning
confidence: 99%
“…Trizol extraction followed by isopropanol precipitation provides a high yield of purified RNA [5], however, it requires extensive labor, is difficult to scale to high-throughput, and involves hazardous materials. Simpler isopropanol precipitation methods, in which patient swab samples are first mixed with commercial or homemade lysis solutions, have been reported to give Ct values comparable to those obtained using commercial RNA purification kits [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…A two-step testing procedure using primer sets targeting the E gene for initial screening followed by the RdRp gene to confirm positive samples is recommended by the German Consiliary Laboratory for Coronaviruses [ 2 ]. The unprecedented global demand for commercial RNA extraction kits and ensuing shortage of these reagents [ 3 ] led to the establishment of several diagnostic workflows performed on patient samples with or without an intermediate RNA extraction step [ 4 , 5 , 6 , 7 ]. Viral RNA isolation from clinical samples depends on the rapid inactivation of viral particles, typically by detergent solubilization, and on the denaturation of omnipresent RNases [ 8 ].…”
Section: Introductionmentioning
confidence: 99%